Additional Diagnostic Value of Fusion Imaging of CEUS and First CEUS of Invisible Hepatic Lesions ≤2 cm. (17th September 2020) - Zhou, Yan; Wang, Yandong; Wang, Fengmei; Zhang, Xiang; Ding, Jianmin; Zhou, Hongyu; Jing, Xiang
Abstract : Objective: To explore the clinical value of image fusion of contrast‐enhanced ultrasonography (CEUS) and contrast‐enhanced computed tomography (CECT) in the diagnosis of invisible lesions with a size ≤2 cm on conventional ultrasound imaging, and compare it with the clinical value of "first CEUS" . Methods: A total of 132 patients with 147 lesions with abnormal blood supply with a size ≤2 cm on CECT were included in this study. "first CEUS" was performed for these lesions. Then "fusion CEUS, " that is, CEUS administered after fusion of US and CECT images, was carried out. The detection rates of the "first CEUS" and "fusion CEUS" were compared. How "fusion CEUS" corrects the misdiagnosis of liver lesions on CECT was analyzed. Results: One hundred nine lesions considered as HCC and 38 lesions considered as benign lesions on CECT were included. The detection rates for the lesions of "first CEUS" and "fusion CEUS" were 71.4% and 96.6%, respectively ( P  < 0.001). Among the 147 lesions, 68 were with a diameter ≤ 1 cm. The detection rate of "first CEUS" and "fusion CEUS" were 55.9% and 95.6%, respectively ( P  < 0.001) for the lesions with a size ≤1 cm. "Fusion CEUS" and "first CEUS" corrected the misdiagnosis in 2 lesions on CECT. Conclusion: The "first CEUS" and "fusion CEUS" can improve the lesion conspicuity. Compared with "first CEUS, " "fusion CEUS" has a higher diagnostic ability and hence can detect most of the invisible lesions on the former. Abstract : Access the CME test here and search by article title.